Method for producing negative electrode active material, negative electrode active material, negative electrode, and secondary battery

By heat-treating silicon-based precursors and ionic compounds to form pore-containing silicon-based particles, and evenly arranging alkali metals and halogen elements on their surfaces and pores, the problem of insufficient conductivity of negative electrode active materials in lithium secondary batteries is solved, and the problem of improved performance of improved The discharge capacity and life characteristics of the battery are as follows.

CN119173475APending Publication Date: 2024-12-20LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380041618.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-31
Filing Date
2023-11-01
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The conductivity of the negative electrode active material in the existing lithium secondary batteries is insufficient, resulting in poor battery life characteristics and discharge capacity, and it is difficult to achieve uniform layout of the carbon layer.

Method used

By heat-treating the silicon-based precursor and ionic compound vaporization, silicon-based particles containing pores are formed, and a carbon layer is uniformly arranged on its surface and pores, including alkali metal elements and halogen elements, and the average diameter of the control pores is between 20nm and 60nm .

Benefits of technology

The conductivity of the negative electrode active material is improved, the discharge capacity, initial efficiency and life characteristics of the battery are enhanced, and the resistance performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing a negative electrode active material, a negative electrode active material, a negative electrode comprising the same, and a secondary battery comprising the same.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for manufacturing a negative electrode active material, a negative electrode active material, a negative electrode, and a secondary battery.

[0002] This application claims the priority and benefits of Korean Patent Application No. 10-2022-0177126, filed with the Korean Intellectual Property Office on December 16, 2022, and Korean Patent Application No. 10-2023-0147653, filed with the Korean Intellectual Property Office on October 31, 2023, the entire contents of which are incorporated herein by reference. Background Art

[0003] In recent years, with the rapid popularization of electronic devices using batteries (such as mobile phones, laptop computers, and electric vehicles, etc.), the demand for small, lightweight, and relatively high-capacity secondary batteries is increasing rapidly. In particular, lithium secondary batteries have attracted much attention as a driving power source for portable devices due to their light weight and high energy density. Therefore, research and development work on improving the performance of lithium secondary batteries are being actively carried out.

[0004] Generally, a lithium secondary battery includes a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, an electrolyte, an organic solvent, etc. In addition, for the positive electrode and the negative electrode, an active material layer containing a positive electrode active material and a negative electrode active material can be formed on a current collector. Generally, for the positive electrode, lithium-containing metal oxides such as LiCoO 2 and LiMn 2 O 4 are used as the positive electrode active material, and for the negative electrode, a carbon-based active material or a silicon-based active material without lithium is used as the negative electrode active material.

[0005] Among the negative electrode active materials, silicon-based active materials have attracted attention because they have higher capacity and excellent high-speed charging characteristics compared to carbon-based active materials. However, the disadvantages of the silicon-based active materials are that the degree of volume expansion / shrinkage during charge and discharge is large, and the irreversible capacity is large, so the initial efficiency is low.

[0006] On the other hand, among the silicon-based active materials, silicon-based oxides, specifically silicon-based oxides represented by SiO x (0 < x < 2), have the advantage that the degree of volume expansion / shrinkage during charge and discharge is lower compared to other silicon-based active materials such as silicon (Si).

[0007] In addition, a technique for forming a carbon layer is used to improve the conductivity of the negative electrode active material. However, with the general method of fabricating a carbon layer, it is difficult to uniformly arrange the carbon layer on the surface and inside of the negative electrode active material, so the improvement in battery life characteristics is not significant.

[0008] Therefore, there is a need to develop a negative electrode active material in which a carbon layer is uniformly disposed on silicon-based particles, and a method for manufacturing the negative electrode active material.

[0009] Citation List

[0010] Patent Document

[0011] (Patent Document 1) Korean Patent Application Publication No. 10-2019-0068476 Summary of the Invention

[0012] Technical Problem

[0013] The present invention relates to a method for manufacturing a negative electrode active material, a negative electrode active material, a negative electrode including the negative electrode active material, and a secondary battery including the negative electrode.

[0014] Technical Solution

[0015] An exemplary embodiment of the present invention provides a method for manufacturing a negative electrode active material, the method including: vaporizing a silicon-based precursor and an ionic compound by heat treatment; forming silicon-based particles by depositing a mixed gas of the silicon-based precursor and the ionic compound in a gas phase; and heat-treating the silicon-based particles and a carbon source.

[0016] An exemplary embodiment of the present invention provides a negative electrode active material manufactured by the method for manufacturing a negative electrode active material.

[0017] An exemplary embodiment of the present invention provides a negative electrode active material including: silicon-based particles containing SiO x (0 < x < 2) and pores; and a carbon layer disposed on a surface and in pores of the silicon-based particles, wherein the negative electrode active material includes one or more alkali metal elements selected from the group consisting of Li, Na, K, Rb, and Cs and one or more halogen elements selected from the group consisting of F, Cl, Br, and I, and wherein when analyzing a cross section of the negative electrode active material, an average diameter of the pores is 20 nm to 60 nm.

[0018] Another exemplary embodiment of the present invention provides a negative electrode including the negative electrode active material.

[0019] Yet another exemplary embodiment of the present invention provides a secondary battery including the negative electrode.

[0020] Advantageous Effects

[0021] The method for manufacturing a negative electrode active material according to an exemplary embodiment of the present invention deposits a silicon-based precursor together with an ionic compound to form silicon-based particles, so that pores are uniformly formed and carbon layers are uniformly arranged, thereby improving the conductivity of the negative electrode active material and improving the discharge capacity, initial efficiency, resistance performance and / or life characteristics of the battery. In addition, the ionic compound that is not removed and remains further improves the conductivity of the negative electrode active material.

[0022] The negative electrode active material according to an exemplary embodiment of the present invention contains one or more alkali metal elements selected from the group consisting of Li, Na, K, Rb and Cs and one or more halogen elements selected from the group consisting of F, Cl, Br and I, and when the cross section of the negative electrode active material is analyzed, the average diameter of the pores is 20nm to 60nm. In the negative electrode active material having the above characteristics, the pores are uniformly formed, the carbon layer is uniformly distributed over a large area on the surface of the negative electrode active material and inside the pores, and contains the alkali metal elements and the halogen elements, so that the conductivity can be improved.

[0023] Therefore, the negative electrode including the negative electrode active material according to an exemplary embodiment of the present invention and the secondary battery including the negative electrode have the effect of improving the discharge capacity, initial efficiency, resistance properties and / or life characteristics of the battery. DETAILED DESCRIPTION

[0024] Hereinafter, this specification will be described in more detail.

[0025] In the present specification, when it is mentioned that a portion “comprises” specific constituent elements, unless otherwise described, this does not mean to exclude other constituent elements but means that the portion may further include other constituent elements.

[0026] Throughout this specification, when it is mentioned that a component is disposed “on” another component, the component may be in direct contact with the other component, or intervening components may also be present.

[0027] It should be understood that the terms or words used throughout the specification should not be interpreted as limited to their usual or dictionary meanings, but should be interpreted with meanings and concepts consistent with the technical spirit of the present invention based on the principle that the inventor can appropriately define the concepts of the terms or words to best interpret the present invention.

[0028] As used herein, the singular forms “a”, “an” and “the” are intended to include the plural forms as well, unless the context clearly indicates otherwise.

[0029] In the present specification, the crystallinity of the structure contained in the negative electrode active material can be confirmed by X-ray diffraction analysis, and the X-ray diffraction analysis can be performed using an X-ray diffraction (XRD) analyzer (trade name: D4-endeavor, manufacturer: Bruker), and in addition to the above-mentioned device, a device commonly used in the field can also be appropriately adopted.

[0030] In the present specification, the presence or absence of elements and the content of the elements in the negative electrode active material may be confirmed by ICP analysis, and the ICP analysis may be performed using an inductively coupled plasma atomic emission spectrometer (ICPAES, Perkin-Elmer 7300).

[0031] In this specification, the average particle size (D 50 ) can be defined as the particle size corresponding to 50% of the cumulative volume in the particle size distribution curve (curve of the particle size distribution diagram). The average particle size (D 50 ) can be measured using, for example, a laser diffraction method. The laser diffraction method is generally capable of measuring particle sizes from the submicron region to the several millimeter range, and can obtain results with high reproducibility and high resolution.

[0032] In the present invention, the specific surface area of ​​the silicon-based composite can be measured by the Brunauer-Emmett-Teller (BET) method. For example, the specific surface area can be measured by the BET six-point method using a nitrogen adsorption method and a porosity analyzer (Bell Japan, Belsorp-II mini).

[0033] In the present invention, the average diameter of the pores (pore size) can be measured by a nitrogen adsorption method according to the BJH (Barrett-Joyner-Halenda) method using a calculation formula. Specifically, the pore area according to the pore size is derived using the BELSORP-mini II model manufactured by BEL Japan, and the pore size representing the maximum pore area is taken as the representative pore size. The BJH method can be used, and in the graph of the measured values, the X-axis is the diameter of the pore (Dp / nm), and the Y-axis is dVp / dDp (cm 3 g -1 nm -1 ).

[0034] Hereinafter, preferred embodiments of the present invention will be described in detail. However, it should be understood that the embodiments of the present invention can be modified in various forms, and the scope of the present invention is not limited to the embodiments described below.

[0035] <Method for producing negative electrode active material>

[0036] An exemplary embodiment of the present invention provides a method for manufacturing a negative electrode active material, the method comprising: gasifying a silicon-based precursor and an ionic compound by heat treatment; forming silicon-based particles by depositing a mixed gas of the silicon-based precursor and the ionic compound together in a gas phase; and heat treating the silicon-based particles and a carbon source.

[0037] When the silicon-based precursor is deposited together with the ionic compound to form silicon-based particles, the ionic compound is distributed in the silicon-based particles. As the ionic compound is removed during the subsequent heat treatment process, pores are uniformly formed in the silicon-based particles, and the carbon layer is uniformly arranged over a large area on the surface of the silicon-based particles and / or inside the pores, thereby improving the conductivity of the negative electrode active material, improving the discharge capacity, initial efficiency, resistance performance and / or life characteristics of the battery. In addition, the ionic compound that is not removed and remains further improves the conductivity of the negative electrode active material.

[0038] The silicon-based precursor may be selected from Si powder, SiO powder and SiO 2 One or more of the group consisting of powders, preferably Si powder, SiO powder and SiO 2 A mixture of powders.

[0039] After the silicon-based precursor and the ionic compound are vaporized by heat treatment in a vacuum, the vaporized mixed gas can be deposited together to form silicon-based particles containing the ionic compound.

[0040] Specifically, the silicon-based precursor and the ionic compound may be vaporized by heat treatment at a temperature of 1800° C. to 2500° C. in an inert gas atmosphere. Specifically, the silicon-based precursor and the ionic compound may be vaporized by heat treatment at a temperature of 2200° C. to 2400° C. At this time, the silicon-based precursor and the ionic compound may be vaporized from different sources and then mixed, or may be vaporized from the same source to form a mixed gas of the silicon-based precursor and the ionic compound.

[0041] The deposition may be performed in an inert gas atmosphere at a temperature of 500° C. to 1000° C. Specifically, the deposition may be performed by heat treatment (cooling) at a temperature of 600° C. to 800° C.

[0042] When the negative electrode active material is manufactured, the silicon-based precursor is deposited together with the ionic compound to manufacture silicon-based particles. At this time, pores can be uniformly formed in the silicon-based particles due to the ionic compound.

[0043] The ionic compound contains one or more alkali metal elements selected from the group consisting of Li, Na, K, Rb, and Cs and one or more halogen elements selected from the group consisting of F, Cl, Br, and I. Specifically, the ionic compound may exist through ionic bonding of an alkali metal element in cation form and a halogen element in anion form. Preferably, the halogen element is Cl, Br, or I, more preferably Cl.

[0044] In an exemplary embodiment of the present invention, the ionic compound may be one or more selected from the group consisting of LiF, LiCl, NaF, and NaCl.

[0045] The ionic compound may have a melting point of 600 °C to 800 °C and a boiling point of 1300 °C to 1700 °C.

[0046] In this case, during the heat treatment of the silicon-based particles, the ionic compound is removed to form pores, and a part of the ionic compound that is not removed remains and exists in the negative electrode active material.

[0047] The weight ratio of the silicon-based precursor to the ionic compound may be 90:10 to 99.9:0.1, or 95:5 to 99:1.

[0048] When manufacturing the negative electrode active material by adding the ionic compound in the above content, an appropriate amount of the ionic compound is added to the silicon-based particles so that pores can be uniformly formed subsequently.

[0049] In an exemplary embodiment of the present invention, the silicon-based particles containing the ionic compound formed during the deposition process may be subjected to additional heat treatment at a temperature of 800 °C to 1100 °C.

[0050] During the additional heat treatment, the ionic compound contained in the silicon-based particles is appropriately removed so that a plurality of pores can be uniformly formed in the silicon-based particles. In addition, a part of the ionic compound that is not removed is contained in the silicon-based particles, further improving the conductivity of the material.

[0051] The silicon-based particles formed as described above may contain SiO x (0 < x < 2), an alkali metal element, and a halogen element. The alkali metal element and the halogen element are derived from the ionic compound that remains without being removed and may be distributed on the surface and / or inside of the silicon-based particles.

[0052] In an exemplary embodiment of the present invention, in order to dope the silicon-based particles with metal (e.g., Li or Mg), the step of gasifying the silicon-based precursor and the ionic compound by heat treatment may include gasifying the metal precursor by heat treatment. Specifically, the metal precursor and the silicon-based precursor and the ionic compound may be gasified from different sources and then mixed, or may be gasified from the same source to form a mixed gas.

[0053] The metal precursor may be vaporized by performing heat treatment at a temperature of 1000° C. to 1400° C. both inclusive.

[0054] The metal precursor may be a Li precursor or a Mg precursor.

[0055] The Li precursor can be, for example, Li powder, LiOH, Li 2 O, etc., but not limited thereto.

[0056] The Mg precursor may be, for example, Mg powder, but is not limited thereto.

[0057] The silicon-based particles formed by further including a Li precursor or a Mg precursor, performing a heat treatment, and then vapor-depositing the mixed gas may also include one or more of a Li compound and a Mg compound. The Li or Mg may be distributed on the surface and / or inside of the silicon-based particles in the form of being doped into the silicon-based particles.

[0058] In another exemplary embodiment, in order to dope the silicon-based particles with a metal (e.g., Li or Mg), after the silicon-based particles and the carbon source are heat-treated, the silicon-based particles and the metal precursor are mixed and then heat-treated. If necessary, this step can be performed under heat treatment, or can be performed using an electrochemical method.

[0059] The step of mixing the silicon-based particles with the metal precursor and then heat-treating them may be performed in an inert atmosphere.

[0060] The step of mixing the formed silicon-based oxide with the metal precursor and then heat-treating the same may be performed in an inert atmosphere at 400° C. to 1400° C., 500° C. to 1000° C., or 700° C. to 900° C. In addition, after the heat treatment, an additional heat treatment may be performed, and the additional heat treatment may be performed at 700° C. to 1100° C. or 800° C. to 1000° C.

[0061] In an exemplary embodiment of the present invention, in order to form a carbon layer on the silicon-based particles, a step of heat-treating the silicon-based particles and a carbon source may be performed.

[0062] The carbon source may be a hydrocarbon gas, but is not limited thereto, and any material known in the art may be used appropriately.

[0063] In the step of heat-treating the silicon-based particles and the carbon source, a carbon layer can be formed on the silicon-based particles by chemical vapor deposition (CVD) or by a method of carbonizing a material as the carbon source.

[0064] The step of heat-treating the silicon-based particles and the carbon source can be carried out at 800 °C to 1200 °C.

[0065] Specifically, the formed silicon-based particles can be placed in a reactor, and then a carbon source (such as a hydrocarbon gas) can be deposited by chemical vapor deposition (CVD) at 600 °C to 1200 °C to form a carbon layer. The hydrocarbon gas can be at least one hydrocarbon gas selected from the group consisting of methane, ethane, propane, and acetylene, and the heat treatment is preferably carried out at 800 °C to 1000 °C.

[0066] In this case, during the heat treatment of the carbon source, the carbon layer is uniformly distributed over a large area on the surface and / or inside the pores of the silicon-based particles, thereby improving the conductivity of the negative electrode active material.

[0067] The particle size of the silicon-based particles can be adjusted by methods such as ball milling, jet milling, or air classification, but the present invention is not limited thereto.

[0068] In an exemplary embodiment of the present invention, the average diameter of the pores contained in the silicon-based particles can be 20 nm or more and 60 nm or less.

[0069] <Negative electrode active material>

[0070] An exemplary embodiment of the present invention provides a negative electrode active material manufactured by the method for manufacturing the negative electrode active material.

[0071] An exemplary embodiment of the present invention provides a negative electrode active material, comprising: silicon-based particles containing SiO x (0 < x < 2) and pores; and a carbon layer provided on the surface and in the pores of the silicon-based particles, wherein the negative electrode active material contains one or more alkali metal elements selected from the group consisting of Li, Na, K, Rb, and Cs and one or more halogen elements selected from the group consisting of F, Cl, Br, and I, and wherein when analyzing a cross-section of the negative electrode active material, the average diameter of the pores is 20 nm to 60 nm.

[0072] Generally, when a carbon layer is formed to improve the conductivity of the negative electrode active material, the carbon layer is only concentratedly coated on the surface of the negative electrode active material, so that the conductivity of the negative electrode active material cannot be fully exerted, and there is a problem of deterioration of battery characteristics.

[0073] On the other hand, since the negative electrode active material according to the present invention uses an ionic compound in the manufacture of the negative electrode active material, a large number of pores satisfying a specific size are formed in the silicon-based particles, so that the carbon layer can be effectively arranged in the pores of the silicon-based particles to increase the carbon coating area. In addition, the conductivity of the material can be improved by the elements derived from the ionic compound remaining inside the negative electrode active material.

[0074] In this specification, providing a carbon layer on the surface of silicon-based particles means that the carbon layer is arranged on the outer surface of the silicon-based particles except for the pores of the particles.

[0075] In this specification, providing a carbon layer in the pores of silicon-based particles means that the carbon layer is arranged on the surface and / or the internal space of the pores contained in the silicon-based particles.

[0076] The negative electrode active material according to an exemplary embodiment of the present invention includes silicon-based particles containing SiO x (0 < x < 2) and pores.

[0077] The SiO x (0 < x < 2) corresponds to the matrix in the silicon-based composite particles. The SiO x (0 < x < 2) may be in a form containing Si and / or SiO 2 , and Si may form a phase. That is, x corresponds to the number ratio of O to Si contained in the SiO x (0 < x < 2). When the silicon-based composite particles contain SiO x (0 < x < 2), the discharge capacity of the secondary battery can be improved.

[0078] In an exemplary embodiment of the present invention, when analyzing the cross-section of the negative electrode active material, the average diameter of the pores may be 20 nm to 60 nm, and specifically, it may be 22 nm to 58 nm, 24 nm to 55 nm, or 30 nm to 50 nm.

[0079] In the present invention, the cross-section analysis of the negative electrode active material can be performed using an ion milling device. Specifically, an electrode sample prepared by coating the negative electrode active material on a copper foil (Cu foil) is milled using a Hitachi IM4000 device. Specifically, each sample can be irradiated with an ion beam at a voltage of 1.5 kV for about 3 to 4 hours, and then the cross-section image is measured using a Hitachi S-4800 SEM. Based on the measured SEM cross-section image, the average diameter of the pores appearing in the cross-section of the negative electrode active material can be obtained.

[0080] The pore diameter obtained through the foregoing cross-sectional analysis is related to the pore diameter inside the negative electrode active material and is different from the pore diameter near the surface of the negative electrode active material measured by the nitrogen adsorption method.

[0081] If the average diameter of the pores is less than 20 nm, it is difficult for the pores to accommodate excessive volume changes of the silicon-based particles, and particle breakage is observed in the long-term cycling behavior, resulting in a rapid decrease in battery capacity. When the average diameter of the pores exceeds 60 nm, due to the small amount of carbon layer coating, the battery resistance increases, and the side reaction between the electrolyte and the silicon-based particles increases, thereby deteriorating the life characteristics of the battery.

[0082] When a carbon layer is formed inside the pores, the average diameter of the pores can be calculated from the diameter of the pores containing the carbon layer.

[0083] In an exemplary embodiment of the present invention, the silicon-based particles may contain one or more of Li compounds and Mg compounds.

[0084] In an exemplary embodiment of the present invention, the silicon-based particles may further contain a Li compound.

[0085] The Li compound may correspond to a dopant in the silicon-based particles. The Li compound may exist in the silicon-based particles in at least one form of lithium atoms, lithium silicates, lithium silicides, and lithium oxides. When the silicon-based particles contain a Li compound, the initial efficiency is improved.

[0086] The Li compound may be distributed on the surface and / or inside the silicon-based particles in a form doped into the silicon-based particles. The Li compound may be distributed on the surface and / or inside the silicon-based particles to control the volume expansion / contraction of the silicon-based particles at an appropriate level and prevent damage to the active material. In addition, in terms of reducing the ratio of the irreversible phase (e.g., SiO 2 ) of the silicon-based particles to improve the efficiency of the negative electrode active material, a Li compound may be included.

[0087] In an exemplary embodiment of the present invention, the Li compound may exist in the form of lithium silicate. The lithium silicate is represented by Li a Si b O c (2≤a≤4, 0<b≤2, 2≤c≤5), and can be divided into crystalline lithium silicate and amorphous lithium silicate. The crystalline lithium silicate may be selected from the group consisting of Li 2 SiO 3 , Li 4 SiO 4 , and Li 2 Si 2 O5 At least one lithium silicate in the form of a group is present in the silicon-based particles, and the amorphous lithium silicate may have Li a Si b O c (2 ≤ a ≤ 4, 0 < b ≤ 2, 2 ≤ c ≤ 5) in a complex form. However, the present invention is not limited thereto.

[0088] In another exemplary embodiment, the Li silicide may contain Li 7 Si 2 , and the lithium oxide may contain Li 2 O.

[0089] In an exemplary embodiment of the present invention, based on a total of 100 parts by weight of the negative electrode active material, the content of Li may be 0.1 part by weight to 40 parts by weight, or 0.1 part by weight to 25 parts by weight. Specifically, the content of Li may be 1 part by weight to 25 parts by weight, more specifically it may be 2 parts by weight to 20 parts by weight, or 2 parts by weight to 10 parts by weight. As the Li content increases, the initial efficiency increases, but the discharge capacity decreases. Therefore, when the above range is satisfied, an appropriate discharge capacity and initial efficiency can be achieved.

[0090] In an exemplary embodiment of the present invention, the silicon-based particles may further contain an Mg compound.

[0091] The Mg compound may correspond to a dopant in the silicon-based particles. The Mg compound may exist in the silicon-based particles in at least one form of a magnesium atom, magnesium silicate, magnesium silicide, and magnesium oxide. When the silicon-based particles contain an Mg compound, the initial efficiency is improved.

[0092] The Mg compound may be distributed on the surface and / or inside of the silicon-based particles in a form doped into the silicon-based particles. The Mg compound may be distributed on the surface and / or inside of the silicon-based particles to control the volume expansion / contraction of the silicon-based particles at an appropriate level and prevent damage to the active material. In addition, in terms of reducing the proportion of the irreversible phase (such as SiO 2 ) of the silicon-based particles to improve the efficiency of the negative electrode active material, an Mg compound may be included.

[0093] In an exemplary embodiment of the present invention, the Mg compound may exist in the form of magnesium silicate. The magnesium silicate may be divided into crystalline magnesium silicate and amorphous magnesium silicate. The magnesium silicate may contain Mg 2 SiO 4 and MgSiO 3 at least one of.

[0094] In another exemplary embodiment, the magnesium silicide may include Mg 2 Si, and the magnesium oxide may include MgO.

[0095] The content of Li element and Mg element can be confirmed by inductively coupled plasma (ICP) analysis. Specifically, a predetermined amount (about 0.01g) of negative electrode active material is accurately weighed, transferred to a platinum crucible and nitric acid, hydrofluoric acid and sulfuric acid are added thereto to completely decompose it on a hot plate. Then, an inductively coupled plasma atomic emission spectrometer (ICP-AES, Perkin-Elmer 7300) is used to measure the intensity of a standard solution prepared using a standard solution (5 mg / kg) at the inherent wavelength of the element to be analyzed to make a reference calibration curve. Thereafter, the pretreated sample solution and the blank sample are introduced into the spectrometer, the actual intensity is calculated by measuring the intensity of each component, the concentration of each component is calculated based on the prepared calibration curve, and the calculated concentration of each component is converted so that the sum of the calculated concentrations of the components is equal to the theoretical value, and the element content of the prepared negative electrode active material can be analyzed.

[0096] In an exemplary embodiment of the present invention, the silicon-based particles may contain additional metal atoms. The metal atoms may be present in the silicon-based particles in the form of at least one of metal atoms, metal silicates, metal silicides, and metal oxides. The metal atoms may contain at least one selected from the group consisting of Mg, Li, Al, and Ca. Thus, the initial efficiency of the negative electrode active material can be improved.

[0097] In an exemplary embodiment of the present invention, a carbon layer may be provided on the surface and in the pores of the silicon-based particles, thereby imparting conductivity to the silicon-based particles and effectively suppressing the volume change of the negative electrode active material including the silicon-based particles, thereby improving the life characteristics of the battery.

[0098] In this case, the carbon layer may cover at least a portion of the surface and the inside of the pores of the silicon-based particles, that is, may partially cover the surface and the inside of the pores of the particles, or may completely cover the surface and the inside of the pores of the particles.

[0099] In an exemplary embodiment of the present invention, the carbon layer includes amorphous carbon.

[0100] Furthermore, the carbon layer may further include crystalline carbon.

[0101] The crystalline carbon may further improve the conductivity of the negative electrode active material. The crystalline carbon may include at least one selected from the group consisting of fullerene, carbon nanotube, and graphene.

[0102] The amorphous carbon can appropriately maintain the strength of the carbon layer to suppress the expansion of the silicon-based particles. The amorphous carbon can be a carbide of at least one substance selected from the group consisting of tar, pitch, and other organic materials, or can be a carbon-based material formed by using hydrocarbons as a source for chemical vapor deposition.

[0103] The carbide of the other organic material may be a carbide of an organic material selected from sucrose, glucose, galactose, fructose, lactose, mannose, ribose, aldohexose or ketohexose, and a combination thereof.

[0104] The hydrocarbon may be a substituted or unsubstituted aliphatic or alicyclic hydrocarbon, or a substituted or unsubstituted aromatic hydrocarbon. The aliphatic or alicyclic hydrocarbon of the substituted or unsubstituted aliphatic or alicyclic hydrocarbon may be methane, ethane, ethylene, acetylene, propane, butane, butene, pentane, isobutane, hexane, etc. The aromatic hydrocarbon of the substituted or unsubstituted aromatic hydrocarbon may be benzene, toluene, xylene, styrene, ethylbenzene, diphenylmethane, naphthalene, phenol, cresol, nitrobenzene, chlorobenzene, indene, coumarone, pyridine, anthracene, phenanthrene, etc.

[0105] In an exemplary embodiment of the present invention, the carbon layer may be an amorphous carbon layer.

[0106] In an exemplary embodiment of the present invention, the content of the carbon layer may be 0.1 to 50 parts by weight, 0.1 to 30 parts by weight, or 0.1 to 20 parts by weight, based on a total of 100 parts by weight of the negative electrode active material. More specifically, the content of the carbon layer may be 0.5 to 15 parts by weight, 1 to 10 parts by weight, or 1 to 5 parts by weight. When the above range is met, the capacity and efficiency of the negative electrode active material can be prevented from being reduced.

[0107] In an exemplary embodiment of the present invention, the thickness of the carbon layer may be 1 nm to 500 nm, specifically 5 nm to 300 nm. When the above range is met, the conductivity of the negative electrode active material is improved, the volume change of the negative electrode active material is easily suppressed, and the side reaction between the electrolyte and the negative electrode active material is suppressed, thereby improving the initial efficiency and / or life of the battery.

[0108] Specifically, the carbon layer may be formed by chemical vapor deposition (CVD) using at least one hydrocarbon gas selected from the group consisting of methane, ethane, and acetylene.

[0109] In an exemplary embodiment of the present invention, the negative electrode active material includes one or more alkali metal elements selected from the group consisting of Li, Na, K, Rb and Cs, and one or more halogen elements selected from the group consisting of F, Cl, Br and I. Specifically, when manufacturing the negative electrode active material, silicon-based particles are manufactured by depositing a silicon-based precursor and an ionic compound containing the alkali metal element and the halogen element together. In this case, the ionic compound allows pores to be uniformly formed in the silicon-based particles, and the silicon-based particles may contain the alkali metal element and the halogen element.

[0110] In one example, the alkali metal element and the halogen element may be located inside pores of the negative active material.

[0111] In an exemplary embodiment of the present invention, the content of the alkali metal element may be 0.01 parts by weight or more and less than 10 parts by weight based on 100 parts by weight of the negative electrode active material. Specifically, the content of the alkali metal element may be greater than 0.01 parts by weight and less than 10 parts by weight, greater than 0.01 parts by weight and less than 5 parts by weight, greater than 0.05 parts by weight and less than 5 parts by weight, greater than 0.05 parts by weight and less than 2.5 parts by weight, greater than 0.05 parts by weight and less than 2 parts by weight, or greater than 0.1 parts by weight and less than 1.5 parts by weight based on 100 parts by weight of the negative electrode active material. In this case, the content of the alkali metal element may refer to the content of the alkali metal element derived from the ionic compound.

[0112] In an exemplary embodiment of the present invention, the content of the halogen element may be 0.01 parts by weight or more and less than 10 parts by weight based on 100 parts by weight of the negative electrode active material. Specifically, the content of the halogen element may be greater than 0.01 parts by weight and less than 10 parts by weight, greater than 0.01 parts by weight and less than 5 parts by weight, greater than 0.05 parts by weight and less than 5 parts by weight, greater than 0.05 parts by weight and less than 2.5 parts by weight, greater than 0.05 parts by weight and less than 2 parts by weight, or greater than 0.1 parts by weight and less than 1.5 parts by weight, based on 100 parts by weight of the negative electrode active material. In this case, the content of the halogen element may represent the content of the halogen element derived from the ionic compound.

[0113] When the alkali metal element and the halogen element in the negative electrode active material are present in the above content, a large number of pores are formed in the silicon-based particles, and the carbon layer is effectively arranged in the pores of the silicon-based particles, thereby increasing the carbon coating area.

[0114] On the other hand, if the alkali metal element and the halogen element are not present in the negative electrode active material, that is, if the ionic compound is not added when the silicon-based particles are manufactured, pores are not formed in the silicon-based particles, and thus the carbon coating area is reduced, and the carbon is only concentrated on the surface of the silicon-based particles, thereby reducing the conductivity of the negative electrode active material and deteriorating the battery characteristics.

[0115] In addition, if the amount of the alkali metal element and the halogen element present exceeds the above content range, the number of pores is small and the average particle size formed is small, resulting in the inability to properly arrange the carbon layer, causing the energy density of the battery to decrease and the discharge capacity, efficiency and / or life characteristics of the battery during cycling behavior to deteriorate.

[0116] In an exemplary embodiment of the present invention, when the alkali metal element and the halogen element in the negative electrode active material are present in the above-mentioned content, the conductivity of the negative electrode active material can be further improved.

[0117] In an exemplary embodiment of the present invention, the negative electrode active material may include Li, Na, or K. Specifically, the negative electrode active material may include at least one alkali metal element of Li and Na.

[0118] In an exemplary embodiment of the present invention, the negative electrode active material may include F or Cl. Specifically, the negative electrode active material may include at least one halogen element of F and Cl. More specifically, the negative electrode active material may include Cl.

[0119] In an exemplary embodiment of the present invention, the negative electrode active material includes an ionic compound. When manufacturing the negative electrode active material, the silicon-based precursor and the ionic compound are deposited together to manufacture the silicon-based particles. At this time, the ionic compound enables pores to be uniformly formed in the silicon-based particles.

[0120] In one example, the ionic compound may be located inside the pores of the negative active material.

[0121] The ionic compound includes one or more alkali metal elements selected from the group consisting of Li, Na, K, Rb and Cs and one or more halogen elements selected from the group consisting of F, Cl, Br and I. Specifically, the ionic compound may exist by ionic bonding of the alkali metal element in the form of a cation and the halogen element in the form of an anion.

[0122] In an exemplary embodiment of the present invention, the ionic compound may be one or more selected from the group consisting of LiF, LiCl, NaF, and NaCl.

[0123] The ionic compound may have a melting point of 600°C to 800°C and a boiling point of 1300°C to 1700°C.

[0124] In this case, during the heat treatment of the silicon-based particles, the ionic compound is removed to form pores, and a portion of the ionic compound that is not removed remains and exists in the negative electrode active material.

[0125] The content of the ionic compound may be greater than 0 parts by weight and less than 10 parts by weight based on 100 parts by weight of the negative electrode active material. Specifically, the content may be greater than 0 parts by weight and less than 5 parts by weight, greater than 0.1 parts by weight and less than 4 parts by weight, or greater than 0.1 parts by weight and less than 3 parts by weight.

[0126] When the ionic compound in the negative electrode active material is present in the above content, a large number of pores are formed in the silicon-based particles, and the carbon layer is effectively arranged in the pores of the silicon-based particles, thereby increasing the carbon coating area.

[0127] On the other hand, if the ionic compound is not present, that is, if the ionic compound is not added when the silicon-based particles are manufactured, no pores are formed in the silicon-based particles, so the carbon coating area is reduced, and the carbon is concentrated only on the surface of the silicon-based particles, thereby reducing the conductivity of the negative electrode active material and deteriorating the battery characteristics. If the ionic compound is present in an amount exceeding the above range, the number of pores is small, the average particle size formed is small, and the carbon layer is improperly arranged, reducing the energy density of the battery.

[0128] In addition, when the ionic compound in the negative electrode active material is present in the above content, the conductivity of the negative electrode active material can be further improved.

[0129] The average particle size of the negative electrode active material (D 50 ) can be 0.1 μm to 30 μm, specifically 1 μm to 20 μm, and more specifically 1 μm to 10 μm. When the above range is met, the structural stability of the active material during charge and discharge is ensured, the problem of increasing the volume expansion / contraction level with excessive increase in particle size can be prevented, and the problem of reduced initial efficiency due to too small particle size can be prevented.

[0130] The BET specific surface area of ​​the negative electrode active material can be 1 m 2 / g to 100m 2 / g, specifically, it can be 1m 2 / g to 70m 2 / g, more specifically, it can be 1m 2 / g to 50m 2 / g, for example, it can be 2m 2 / g to 30m2 When the above range is met, the side reaction between the electrolyte and the negative electrode active material during the battery charge and discharge process can be reduced, thereby improving the life characteristics of the battery.

[0131] <Negative electrode>

[0132] A negative electrode according to an exemplary embodiment of the present invention may include the above-mentioned negative electrode active material.

[0133] Specifically, the negative electrode may include a negative electrode current collector and the negative electrode active material layer disposed on the negative electrode current collector. The negative electrode active material layer may include the negative electrode active material. In addition, the negative electrode active material layer may further include a binder, a thickener and / or a conductive material.

[0134] The negative electrode active material layer may be formed by applying a negative electrode slurry including a negative electrode active material, a binder, a thickener and / or a conductive material to at least one surface of a current collector, and drying and rolling it.

[0135] The negative electrode slurry may further include additional negative electrode active materials.

[0136] As the additional negative electrode active material, a compound capable of reversibly intercalating and deintercalating lithium may be used. Specific examples include: carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metal substances capable of alloying with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy, or Al alloy; metal oxides capable of doping and dedoping lithium, such as SiO β (0<β<2), SnO 2 , vanadium oxide, lithium titanium oxide and lithium vanadium oxide; or a composite containing a metal substance and a carbonaceous material, such as a Si-C composite or a Sn-C composite, and any one thereof or a mixture of two or more thereof can be used. In addition, a metallic lithium film can be used as the negative electrode active material. In addition, both low-crystalline carbon and high-crystalline carbon can be used as the carbon material. Representative examples of the low-crystalline carbon include soft carbon and hard carbon, and representative examples of the high-crystalline carbon include amorphous, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite, floating graphite, pyrolytic carbon, mesophase pitch-based carbon fibers, mesophase carbon microbeads, mesophase pitch, and high-temperature fired carbon (e.g., coke from petroleum or coal tar pitch).

[0137] The additional negative electrode active material may be a carbon-based negative electrode active material.

[0138] The negative electrode slurry may include a solvent for forming the negative electrode slurry. Specifically, from the perspective of facilitating the dispersion of components, the solvent for forming the negative electrode slurry may include at least one selected from the group consisting of distilled water, ethanol, methanol, and isopropanol, specifically distilled water.

[0139] The negative electrode slurry including the negative electrode active material according to an exemplary embodiment of the present invention may have a pH of 7 to 11 at 25° C. When the pH of the negative electrode slurry satisfies the above range, the rheological properties of the slurry are stabilized. On the other hand, when the pH of the negative electrode slurry is less than 7 or the pH of the negative electrode slurry exceeds 11, carboxymethyl cellulose (CMC) used as a thickener decomposes, resulting in a decrease in the viscosity of the slurry and a decrease in the dispersion of the active material contained in the slurry.

[0140] The negative electrode current collector is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. For example, as the current collector, copper, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel that has been surface-treated with carbon, nickel, titanium, silver, etc., can be used. Specifically, a transition metal such as copper or nickel that adsorbs carbon well can be used as a current collector. The thickness of the current collector can be 6 μm to 20 μm. However, the thickness of the current collector is not limited thereto.

[0141] The binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid and the above materials in which hydrogen is replaced by Li, Na, Ca, etc., and may also include various copolymers thereof.

[0142] There is no particular limitation on the conductive material as long as it has conductivity and does not cause chemical changes to the battery. For example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; conductive fibers such as carbon fibers and metal fibers; conductive tubes such as carbon nanotubes; metal powders such as fluorocarbon powders, aluminum powders and nickel powders; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc. can be used.

[0143] The thickener may be carboxymethyl cellulose (CMC), and is not limited thereto, and a thickener used in the art may be appropriately employed.

[0144] In an exemplary embodiment of the present invention, a weight ratio of the negative electrode active material and the additional negative electrode active material included in the negative electrode slurry may be 1:99 to 30:70, specifically 5:95 to 30:70 or 10:90 to 20:80.

[0145] In an exemplary embodiment of the present invention, the content of all negative electrode active materials contained in the negative electrode slurry may be 60 to 99 parts by weight, specifically 70 to 98 parts by weight, based on a total of 100 parts by weight of solid content of the negative electrode slurry.

[0146] In an exemplary embodiment of the present invention, the binder may be included in an amount of 0.5 to 30 parts by weight, for example 1 to 20 parts by weight, based on a total of 100 parts by weight of solid content of the negative electrode slurry.

[0147] In an exemplary embodiment of the present invention, the content of the conductive material may be 0.5 to 25 parts by weight, specifically 1 to 20 parts by weight, based on a total of 100 parts by weight of the solid content of the negative electrode slurry.

[0148] In an exemplary embodiment of the present invention, the thickener may be included in an amount of 0.5 to 25 parts by weight, specifically 0.5 to 20 parts by weight, more specifically 1 to 20 parts by weight, based on a total of 100 parts by weight of the solid content of the negative electrode slurry.

[0149] The negative electrode slurry according to an exemplary embodiment of the present invention may further include a solvent for forming the negative electrode slurry. Specifically, from the perspective of facilitating the dispersion of components, the negative electrode slurry forming solvent may include at least one selected from the group consisting of distilled water, ethanol, methanol and isopropanol, specifically distilled water.

[0150] In an exemplary embodiment of the present invention, the solid content of the negative electrode slurry may be 20 to 75 parts by weight, specifically 30 to 70 parts by weight, based on a total of 100 parts by weight of the negative electrode slurry.

[0151] <Secondary Battery>

[0152] The secondary battery according to the exemplary embodiment of the present invention may include the negative electrode according to the exemplary embodiment of the present invention described above. Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, and the negative electrode is the same as the negative electrode described above. Since the negative electrode has been described above, its specific description is omitted.

[0153] The positive electrode may include a positive electrode collector and a positive electrode active material layer formed on the positive electrode collector and including a positive electrode active material.

[0154] In the positive electrode, there is no particular restriction on the positive electrode collector, as long as the positive electrode collector has conductivity and does not cause chemical changes to the battery. For example, stainless steel, aluminum, nickel, titanium, fired carbon, aluminum or stainless steel each surface-treated with carbon, nickel, titanium, silver, etc., etc. can be used. In addition, the positive electrode collector can generally have a thickness of 3 to 500 μm, and fine concavoconvexities can be formed on the surface of the collector to enhance the adhesion of the positive electrode active material. For example, the positive electrode collector can be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.

[0155] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO 2 ) and lithium nickel oxide (LiNiO 2 ), or compounds substituted by one or more transition metals; lithium iron oxides, such as LiFe 3 O 4 ; Lithium manganese oxide, such as Li 1+c1 Mn 2-c1 O 4 (0≤c1≤0.33), LiMnO 3 、LiMn 2 O 3 and LiMnO 2 ; Lithium copper oxide (Li 2 CuO 2 ); Vanadium oxides, such as LiV 3 O 8 、V 2 O 5 and Cu 2 V 2 O 7 ; Ni-site lithium nickel oxide, with chemical formula LiNi 1-c2 M c2 O 2 (wherein M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B and Ga, and satisfies 0.01≤c2≤0.3); lithium manganese composite oxide, represented by the chemical formula LiMn 2-c3 M c3 O 2 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn and Ta, and satisfies 0.01≤c3≤0.1) or Li 2 Mn 3MO 8 (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu and Zn); wherein a portion of Li in the chemical formula is replaced by an alkaline earth metal ion LiMn 2 O 4 The positive electrode may be Li metal.

[0156] The positive electrode active material layer may further include a positive electrode conductive material and a positive electrode binder in addition to the positive electrode active material.

[0157] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without particular limitation, as long as the positive electrode conductive material has electronic conductivity without causing chemical changes in the constituted battery. Specific examples may include: graphite, such as natural graphite or artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber, such as copper, nickel, aluminum, and silver; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, etc., and any one thereof or a mixture of two or more thereof may be used.

[0158] In addition, the positive electrode binder is used to improve the bonding between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode collector. Specific examples may include: polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber or various copolymers thereof, and any one thereof or a mixture of two or more thereof may be used.

[0159] The diaphragm is used to separate the negative electrode and the positive electrode, and provides a mobile channel for lithium ions, wherein any diaphragm can be used as the diaphragm without particular restriction, as long as it is commonly used in secondary batteries, in particular, it is preferred to use a diaphragm with high electrolyte moisture retention ability and low resistance to the movement of electrolyte ions. Specifically, a porous polymer film can be used, for example, a porous polymer film manufactured by a polyolefin-based polymer (such as, ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer and ethylene / methacrylate copolymer), or a laminated structure of more than two layers thereof. In addition, conventional porous nonwoven fabrics can be used, such as nonwoven fabrics formed by high melting point glass fiber, polyethylene terephthalate fiber, etc. In addition, a coated diaphragm comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a diaphragm with a monolayer or multilayer structure can be selectively used.

[0160] Examples of the electrolyte may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, a molten inorganic electrolyte, etc., which may be used to prepare a lithium secondary battery, but are not limited thereto.

[0161] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.

[0162] As the nonaqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ether, methyl propionate or ethyl propionate can be used.

[0163] Especially, in the carbonate-based organic solvent, ethylene carbonate and propylene carbonate as cyclic carbonate have high dielectric constant as high viscosity organic solvent, thus well dissociate lithium salt, therefore can be preferably used.When the cyclic carbonate is mixed with low viscosity and low dielectric constant linear carbonate (such as dimethyl carbonate or diethyl carbonate) in an appropriate ratio, an electrolyte with high conductivity can be prepared, therefore can be more preferably used.

[0164] As the metal salt, a lithium salt can be used. The lithium salt is a material that is easily dissolved in a non-aqueous electrolyte. For example, as the anion of the lithium salt, a metal salt selected from the group consisting of F - , Cl- 、I - 、NO 3 - 、N(CN) 2 - 、BF 4 - 、ClO 4 - 、PF 6 - 、(CF 3 ) 2 PF 4 - 、(CF 3 ) 3 PF 3 - 、(CF 3 ) 4 PF 2 - 、(CF 3 ) 5 PF - 、(CF 3 ) 6 P - 、CF 3 SO 3 - 、CF 3 CF 2 SO 3 - 、(CF 3 SO 2 ) 2 N - 、(FSO 2 ) 2 N - 、CF 3 CF 2 (CF 3 ) 2 CO - 、(CF 3 SO 2 ) 2 CH - 、(SF 5 ) 3 C - 、(CF 3 SO 2 ) 3 C - 、CF 3 (CF 2 ) 7 SO 3 - 、CF 3 CO 2- , CH 3 CO 2 - 、SCN - and (CF 3 CF 2 SO 2 ) 2 N - One or more of the groups consisting of.

[0165] In the electrolyte, in order to improve the service life characteristics of the battery, inhibit the reduction of the battery capacity and improve the discharge capacity of the battery, in addition to containing the above-mentioned electrolyte components, one or more additives may be included, for example, halogenated alkylene carbonate compounds (such as difluoroethylene carbonate), pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme dimethyl ether, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum trichloride.

[0166] Another exemplary embodiment of the present invention provides a battery module including the secondary battery as a unit cell, and a battery pack including the battery module. Since the battery module and the battery pack include the secondary battery having high capacity, high rate capability, and high cycle characteristics, the battery module and the battery pack can be used as a power source for medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0167] The following will describe the embodiments in detail to specifically describe this specification. However, the embodiments according to this specification can be modified in other forms, and the scope of the present application should not be understood to be limited to the following embodiments. The embodiments of the present application are provided to explain this specification more completely to those skilled in the art.

[0168] Invented Patterns

[0169] <Examples and Comparative Examples>

[0170] Example 1

[0171] Si and SiO mixed in a 1:1 molar ratio 2 900 g of the powder and 10 g of the ionic compound (NaCl) were appropriately mixed and heated to a sublimation temperature of 2,400°C in a reactor under vacuum. Then, the vaporized Si and SiO 2The mixed gas of the ionic compound reacts in a cooling zone under a vacuum state at a cooling temperature of 800°C and condenses into a solid phase. Then, a heat treatment is performed at a temperature of 800°C in an inert atmosphere to prepare preliminary silicon-based particles. Thereafter, the preliminary silicon-based particles are pulverized for 3 hours using a ball mill using 15 SUS ball media to prepare a 6 μm (D 50 Then, while keeping an inert atmosphere by flowing argon gas, the silicon-based particles were placed in a hot zone of a CVD device, and methane was blown into the hot zone at 900° C. using Ar as a carrier gas. -1 The reaction was carried out under support for 5 hours, thereby forming a carbon layer on the surface of the silicon-based particles.

[0172] The silicon-based particles having the carbon layer formed thereon and lithium metal powder as a lithium precursor were solid-phase mixed at a weight ratio of 90:10 to prepare a composition for forming a negative electrode active material.

[0173] The negative electrode active material-forming composition was heat-treated at 800° C. for 3 hours.

[0174] The heat-treated negative electrode active material-forming composition was subjected to an acid treatment in a hydrochloric acid aqueous solution at 23° C. and pH 1 for 1 hour to prepare a negative electrode active material.

[0175] The negative electrode active material has a Na content of 1.5 wt % and a Cl content of 1.2 wt %.

[0176] Example 2

[0177] A negative electrode active material was prepared in the same manner as in Example 1, except that the heat treatment performed after the mixed gas was condensed was performed at 860°C.

[0178] The Na content of the negative electrode active material was 1.3 wt %, and the Cl content was 1.0 wt %.

[0179] Example 3

[0180] A negative electrode active material was prepared in the same manner as in Example 1, except that the heat treatment performed after the mixed gas was condensed was performed at 900°C.

[0181] The Na content of the negative electrode active material was 0.7 wt %, and the Cl content was 0.7 wt %.

[0182] Example 4

[0183] A negative electrode active material was prepared in the same manner as in Example 1, except that the heat treatment performed after the mixed gas was condensed was performed at 1100°C.

[0184] The negative electrode active material had a Na content of 0.1 wt % and a Cl content of 0.1 wt %.

[0185] Example 5

[0186] A negative electrode active material was prepared in the same manner as in Example 1, except that LiCl was used instead of NaCl.

[0187] The negative electrode active material had a Li content of 6.2 wt % and a Cl content of 1.5 wt %. In this case, the Li content derived from the ionic compound was 1.2 wt %, and the Li content derived from the lithium precursor was 5 wt %.

[0188] Example 6

[0189] A negative electrode active material was prepared in the same manner as in Example 1, except that Mg metal powder was used instead of Li metal powder.

[0190] The Na content of the negative electrode active material was 1.4 wt %, and the Cl content was 1.3 wt %.

[0191] Comparative Example 1

[0192] A negative electrode active material was prepared in the same manner as in Example 1 except that the ionic compound was not mixed.

[0193] Comparative Example 2

[0194] A negative electrode active material was prepared in the same manner as in Example 1, except that the heat treatment performed after the mixed gas was condensed was performed at 700°C.

[0195] Comparative Example 3

[0196] A negative electrode active material was prepared in the same manner as in Example 1, except that the heat treatment performed after the mixed gas was condensed was performed at 600°C.

[0197] Comparative Example 4

[0198] A negative electrode active material was prepared in the same manner as in Example 1, except that the heat treatment performed after the mixed gas was condensed was performed at 650°C.

[0199] Comparative Example 5

[0200] A negative electrode active material was prepared in the same manner as in Example 1, except that the heat treatment performed after the mixed gas was condensed was performed at 500°C.

[0201] Comparative Example 6

[0202] A negative electrode active material was prepared in the same manner as in Comparative Example 1, except that Mg metal powder was used instead of Li metal powder.

[0203] <Carbon layer content analysis>

[0204] The content of the carbon layer was analyzed using a CS analyzer (CS-800, ELTRA Corporation).

[0205] <Element content analysis>

[0206] The element content (wt %) of the negative electrode active material was confirmed using SEM-EDS (JEOL Corporation; JSM-7610F).

[0207] The cross section of the negative electrode active material was prepared using an ion milling device. First, the electrode sample prepared by coating the negative electrode active material on the copper foil was milled using a Hitachi IM4000 device. Specifically, each sample was irradiated with an ion beam at a voltage of 1.5 kV for about 3 to 4 hours, and then the entire SEM cross-sectional image was subjected to EDS measurement to determine the element content inside the material.

[0208] <Cross-sectional analysis of negative electrode active material (average diameter measurement)>

[0209] The negative electrode active material was subjected to cross-sectional analysis using an ion milling device. First, the electrode sample prepared by coating the negative electrode active material on the copper foil was milled using a Hitachi IM4000 device. Specifically, each sample was irradiated with an ion beam at a voltage of 1.5 kV for about 3 to 4 hours, and then the cross-sectional image was measured using a Hitachi S-4800 SEM. Next, the average diameter of the pores appearing in the cross section of the negative electrode active material was calculated based on the measured SEM cross-sectional image.

[0210] <D of negative electrode active material 50 Analysis of specific surface area>

[0211] The D of the negative electrode active material was analyzed by laser diffraction particle size analysis using a Microtrac S3500 instrument. 50 The BET specific surface area of ​​the negative electrode active material was measured using a BET measuring instrument (BEL-SORP-MAX, Bell Company, Japan).

[0212]

[0213] <Experimental Example: Evaluation of Conductivity of Negative Electrode Active Material>

[0214] The conductivity of the negative electrode active material was measured using a powder resistance measuring device (HPRM-1000, HANTECH CO). 3 g of the sample (negative electrode active material) was evenly placed in a cylindrical mold with a diameter of 20 mm, and the resistance was measured every 400 kgf from 400 kgf to 2000 kgf, and the conductivity of the negative electrode active material was relatively evaluated in Table 2 below with reference to Example 1.

[0215] <Experimental Example: Evaluation of Discharge Capacity, Initial Efficiency, and Life (Capacity Retention Rate) Characteristics>

[0216] A negative electrode and a battery were manufactured using the negative electrode active materials of the example and the comparative example, respectively.

[0217] The negative electrode active material, carbon black as a conductive material, and polyacrylic acid (PAA) as a binder were mixed in a weight ratio of 80:10:10 to prepare a mixture. Then, 7.8 g of distilled water was added to 5 g of the mixture and then uniformly mixed to prepare a negative electrode slurry. The negative electrode slurry was applied on a copper (Cu) metal film having a thickness of 15 μm as a negative electrode collector and dried. At this time, the temperature of the circulating air was 60°C. Then, the film was rolled and dried in a vacuum oven at 130°C for 12 hours to prepare a negative electrode.

[0218] The prepared electrode as the negative electrode and the positive electrode were cut into 1.7671 cm 2 A porous polyethylene separator is inserted between the circular lithium metal films, and an electrolyte is injected to manufacture a lithium coin-type half-cell. The electrolyte is obtained by dissolving 0.5 parts by weight of vinylene carbonate in a mixed solution of ethyl methyl carbonate (EMC) and ethylene carbonate (EC) in a volume ratio of 7:3, and dissolving LiPF 6 to 1M concentration.

[0219] The prepared battery was charged and discharged, and the discharge capacity, initial efficiency and capacity retention rate were evaluated, as shown in Table 2 below.

[0220] The first and second cycles were charged and discharged at 0.1 C, and the third to 49th cycles were charged and discharged at 0.5 C. The final cycle was completed in a charged state (a state in which the negative electrode contained lithium).

[0221] Charging conditions: CC (constant current) / CV (constant voltage) (5mV / 0.005C current cutoff)

[0222] Discharge conditions: CC (constant current) condition 1.5V

[0223] The discharge capacity (mAh / g) and initial efficiency (%) are obtained from the results after one charge and discharge. Specifically, the initial efficiency (%) is obtained by the following calculation.

[0224] Initial efficiency (%) = (one discharge capacity / one charge capacity) × 100

[0225] The capacity retention rate was calculated as follows.

[0226] Capacity retention rate (%) = (49 discharge capacity / 1 discharge capacity) × 100

[0227]

[0228] According to Table 2, in the negative electrode active materials containing alkali metal elements and halogen elements and having a pore size of 20 nm to 60 nm in Examples 1 to 6, the carbon layer is effectively arranged in the pores of the silicon-based particles, so that the carbon coating area is large, and the conductivity is improved by the ions remaining inside the negative electrode active material. Therefore, it can be confirmed that the discharge capacity, efficiency and / or life characteristics are improved.

[0229] On the other hand, when the negative electrode active material does not contain an alkali metal element and a halogen element as in Comparative Examples 1 and 6, it can be confirmed that no pores are formed, the conductivity is not improved, and therefore the initial efficiency and / or life characteristics are poor. Even when an alkali metal (e.g., lithium) or an alkaline earth metal (e.g., magnesium) is contained in the active material particles as in Comparative Examples 1 and 6, if an ionic compound is not added when preparing the preliminary silicon-based particles, a suitable pore size of the active material particles cannot be achieved.

[0230] In Comparative Examples 2 to 5, it can be confirmed that although the conductivity is improved due to the excessive content of ionic compounds in the negative electrode active material, the capacity of the material is reduced due to the excessive content of ionic compounds, and the discharge capacity, efficiency and / or life characteristics of the battery are significantly deteriorated during the cycle behavior.

Claims

1. A method for producing a negative electrode active material, the method comprising: vaporizing the silicon-based precursor and the ionic compound by heat treatment; forming silicon-based particles by depositing a mixed gas of the silicon-based precursor and the ionic compound together in a gas phase; as well as The silicon-based particles and the carbon source are heat-treated.

2. The method according to claim 1, wherein the silicon-based precursor is a mixed powder of Si powder, SiO powder and SiO2 powder. 3 . The method according to claim 1 , wherein the ionic compound comprises one or more alkali metal elements selected from the group consisting of Li, Na, K, Rb, and Cs and one or more halogen elements selected from the group consisting of F, Cl, Br, and I. The method according to claim 1 , wherein the ionic compound is one or more selected from the group consisting of LiF, LiCl, NaF, and NaCl. 5 . The method according to claim 1 , wherein the depositing is performed in an inert gas atmosphere and at a temperature of 500° C. or higher and 1000° C. or lower. 6 . The method according to claim 1 , wherein the heat treatment of the silicon-based particles and the carbon source is performed at 800° C. to 1200° C. 7 . A negative electrode active material produced by the method for producing a negative electrode active material according to claim 1 .

8. A negative electrode active material comprising: Silicon-based particles containing SiO x (where 0 < x < 2) and pores; and A carbon layer is provided on the surface of the silicon-based particles and in the pores, in, The negative electrode active material comprises one or more alkali metal elements selected from the group consisting of Li, Na, K, Rb and Cs and one or more halogen elements selected from the group consisting of F, Cl, Br and I, and When a cross section of the negative electrode active material is analyzed, an average diameter of the pores is 20 nm to 60 nm. 9 . The negative electrode active material according to claim 8 , wherein the negative electrode active material comprises at least one alkali metal element of Li and Na. 10 . The negative electrode active material according to claim 8 , wherein the negative electrode active material comprises at least one halogen element of F and Cl.

11. The negative electrode active material according to claim 8, wherein the alkali metal element is one or more selected from the group consisting of Na, K, Rb and Cs, and in, The alkali metal element may be present in an amount of greater than 0.01 parts by weight and less than 10 parts by weight based on 100 parts by weight of the negative electrode active material.

12. The negative electrode active material according to claim 8, wherein the halogen element is one or more selected from the group consisting of Cl, Br and I, and in, The content of the halogen element is greater than 0.01 parts by weight and less than 10 parts by weight based on 100 parts by weight of the negative electrode active material. 13 . The negative electrode active material according to claim 8 , wherein the alkali metal element and the halogen element are located inside the pores.

14. The negative electrode active material according to claim 8, wherein The carbon layer may be included in an amount of 0.1 parts by weight to 50 parts by weight based on 100 parts by weight of the negative electrode active material in total. 15 . The negative electrode active material according to claim 8 , wherein the silicon-based particles further contain a Li compound or a Mg compound. 16 . A negative electrode comprising the negative electrode active material according to claim 8 . 17 . A secondary battery comprising the negative electrode according to claim 16 .

Citation Information

Patent Citations

  • Anode Active Material for lithium secondary battery and Method for preparing the same

    KR1020190068476A

  • Light source module and LED film including the same

    KR1020230147653A